Pengaruh Talent Management Terhadap Employee Retention Pada Bank BTN Kantor Cabang Syariah Medan - Nasution, Muhammad Teddy; Nasution, Salman (Universitas Labuhanbatu, 2022)
The purpose of this study was to determine the effect of talent management on employee retention at Bank BTN KC Syariah Medan. The type of researcher using quantitative research that is associative is a process of finding knowledge that uses data in the form of numbers as a tool to find information about what you want to know. The quantitative approach was chosen to explain the influence of talent management on employee retention, whether or not it could be better. Data collection techniques used in this study are questionnaires and documentation. The analytical model used in this study is a simple regression analysis model, using the hypothesis test method with the Rsquare test. Partial test results show that Talent management has an effect on employee retention. And on the R-Square value, the Adjusted RSquare coefficient of determination is 0.749 or 74.9%, meaning that the Talent Management variable affects the Employee Retention variable by 74.9%, while the remaining 25.1% can be explained from other variables outside the research variables.